Therapies for people hospitalized with COVID-19 and alignment with national clinical guidelines in a large hospital, Almaty, Kazakhstan, 2020–2021 - Gazezova, Saya; Nabirova, Dilyara; Detmar, Ariana; Smagul, Manar; Kasabekova, Lena; Zikriyarova, Sanam; Horth, Roberta (Frontiers in Medicine, 2023)
Background: Clinical practice guidelines were continually changing during the COVID-19 pandemic. In Kazakhstan, it was not known to what extent guidelines were followed. Methods: We conducted a sub-analysis of data collected from an observational study among people hospitalized with COVID-19 in a large infectious disease hospital in Almaty in four cross-sections of increased COVID-19 incidence: T1 (June 1-August 30, 2020); T2 (October 1-31 December 2020); T3 (April 1-May 31, 2021); and T4 (July 1-October 26, 2021). Modifications to the national COVID-19 treatment guidelines were identified and clinical data were abstracted from electronic medical records. We used multivariable logistic regression to compare practices across periods. Results: Six modifications were made to national COVID-19 treatment guidelines during this study. Of 1,146 people hospitalized with COVID-19, 14% were in T1, 14% in T2, 22% in T3, and 50% in T4. Anticoagulant treatment was administered to 87% (range: 56-95%), antibiotic treatment to 60% (58-64%), glucocorticoid to 55% (43-56%) and antiviral therapy 15% (7-22%). Majority of treatments were not aligned with national guidelines, including 98% of anticoagulant use, 95% of antibiotic use, 56% of glucocorticoid use, and 56% of antiviral use. There were no changes in practice following changes in guidelines for antibiotic use. There was significant increase in use of anticoagulant, glucocorticoid, and antiviral treatment after guidelines updates. Conclusion: The majority of treatments administered were not aligned with updated clinical guidelines. Increased awareness and training on clinical practice guidelines as updates are released may help improve adoption of evidence-based practices.